Urease Inhibitory Activity of Some Iranian Medicinal Plants - Gohari, A.R.; Nabati, F.; Saeidnia, S.; Malmir, M.; Amanlou, M. (Asian Journal of Chemistry, 2011)
Medicinal plants are enriched of phytoconstituents which found to be urease inhibitors. Bacterial ureases are playing an important role in the pathogenesis of many illnesses. Urease inhibitory assays are the noteworthy tools to guide the isolation and identification of promising natural resources for discovery of novel bioactive compounds as the safe and potent antiulcer drugs. In this paper, we report the evaluation of some Iranian medicinal plants for their possible urease inhibitor activity which have not been previously reported. The ethyl acetate and methanol extracts of the plant materials were tested by enzyme assay using Berthelot alkaline phenol-hypochlorite method. The methanol extracts of Salvia macrosiphon and Stachys byzanthina indicated considerable inhibitory activities 56.35 and 93.12 %, respectively. Apiaceae samples (Lomatopodium staurophyllum and Pimpinella tragioides) showed no inhibitory activity. All samples of Lamiaceae species, except one, Lagochilus cabulicus, showed inhibitory activity in the range of 0.17-93.12 %.